Southernising criminology and global social indicators - Nelken, David (Southernising criminology, 2024)
This chapter asks what those advocating a Southernising ‘turn’ can learn from and teach those arguing about the merits of so-called global social indicators. It first says something about the relationship between these two enquiries. It then goes on to discuss three of the ways Southernising criminologists can and do respond to the challenge of global social indicators, using, as an example, the role of indicators in measuring progress towards meeting the UN sustainable development goals in relation to issues of criminal and social justice.